Development and validation of a headspace GC-MS method to evaluate the interconversion of impurities and the product quality of liquid hand sanitizers - Nicolas Abrigo; Connie Ruzicka; Patrick Faustino; Neil Stiber; Agnes NguyenPho; Thomas O'Connor; Diaa Shakleya (SpringerOpen, 2022)
Abstract The COVID-19 pandemic has led to increased usage of hand sanitizer products by the public to prevent the spread of COVID-19 and decrease the likelihood of acquiring the disease. The increase in demand has also led to an increase in the number of manufacturers. This work describes the FDA's Center for Drug Evaluation and Research (CDER) laboratories efforts to develop tests to assess the quality of hand sanitizer products containing ethanol or isopropanol as the primary active ingredient. The products were evaluated for the active ingredient content and determination of the 12 impurities listed in the FDA Hand Sanitizer Temporary Guidance, followed by a spike recovery assay performed to verify the test results. Extensive method development was conducted including an investigation into the stability of ethanol, isopropanol, and the 12 impurities. Stability and kinetic studies confirmed the instability of acetal in acidic liquid hand sanitizer products during spike recovery assay testing. The headspace GC-MS method was validated according to ICH Q2 (R1) guidelines and the spike recovery assay was validated using three concentrations of standards for the drug product. During method application, six liquid hand sanitizer products were tested and all were determined to have ethanol or isopropanol above 70% v/v. Two liquid hand sanitizer products were determined to contain acetaldehyde as an impurity above the FDA recommended safety levels.